2012
DOI: 10.5539/ass.v8n8p28
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Impacts and Support for Tourism Development in Ha Long Bay, Vietnam: An Examination of Residents’ Perceptions

Abstract: The impacts of tourism have been given much attention by scholars attempting to examine the perceptions as well as attitudes of the local residents toward tourism. Such studies have been carried out thoroughly in the context of the developed countries. However, very little research has been carried out in developing countries. This study attempts to make a little contribution to the sustainable development of tourism by examining the residents' profile, perceptions and attitudes towards tourism impacts and tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 42 publications
(63 reference statements)
1
9
0
4
Order By: Relevance
“…According to the frequency outcomes of the negative tourism impacts perception, 71.9% of respondents disagreed with the statement "Tourism in Ba Be National Park interferes with residents' daily economic activities". This finding is consistent with Pham and Kayat's results in two research projects in Cuc Phuong National Park and Ha Long Bay, Vietnam (Pham and Kalsom 2011;Pham 2012).…”
Section: Respondents' Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…According to the frequency outcomes of the negative tourism impacts perception, 71.9% of respondents disagreed with the statement "Tourism in Ba Be National Park interferes with residents' daily economic activities". This finding is consistent with Pham and Kayat's results in two research projects in Cuc Phuong National Park and Ha Long Bay, Vietnam (Pham and Kalsom 2011;Pham 2012).…”
Section: Respondents' Characteristicssupporting
confidence: 91%
“…Many studies on this subject typically seek the level of residents' support for tourism development in one or more regions, and the factors influencing local attitudes (Perdue et al 1990; Ko and Stewart 2002;McGehee and Andereck 2004;Vargas-S anchez et al 2009; L atkov a and Vogt 2012). Concerning tourism in Vietnam, studies of residents' attitudes have been previously conducted by Pham and Kayat (2011) and Pham (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Long [10] investigated the support for tourism development in Ha Long Bay, Vietnam. The research results indicated that residents viewed tourism positively and would support further development because of the economic and socio-cultural benefits tourism provides.…”
Section: Residents' Attitudes Toward Tourism Development In World Hermentioning
confidence: 99%
“…There have been a number of studies focused on local residents' attitudes in World Heritage Sites [4][5][6][7][8][9][10][11][12][13][14], but there has not been any research dealing with local residents' attitudes towards different forms of tourism development (CTD and SITD). Therefore, this paper could be potentially valuable for those researchers who explore local residents' attitudes toward special interest tourism development generally and in World Heritage Sites.…”
Section: Introductionmentioning
confidence: 99%
“…Over-commercialization in heritage sites, accompanied by a rapid surge in the number of visitors, can bring about negative externalities such as degradation of historic authenticity (Bianchi & Boniface, 2002). Traffic congestion, pollution, and noise are the major adverse environmental impacts (Bieletto-Bueno, 2017;Chen & Chen, 2010;Pham, 2012) that detract from the sustainable development of many tourist-destined communities.…”
Section: Literature Reviewmentioning
confidence: 99%